Implementation of a Preventative Health Series at a Student-Run Free Clinic - Shelly Sharma; Wali Kamran; Mark Conforti; Patrick Tempera; Alessia Cooney; Rebecca Fliorent; Sweta Mukhopadhyay; Nils Brolis (Journal of Student-Run Clinics, 2023)
The Rowan Community Health Clinic (RCHC), located in a small community in southern New Jersey, strives to promote positive healthcare experiences as part of its service in a largely underserved area. A significant number of RCHC’s patients are immigrants, lack primary care physicians, or have difficulty communicating with doctors. Many of them demonstrate limited health literacy, which has been associated with mismanagement of health conditions, increased costs, and distrust of physicians. Lack of opportunities for health education may contribute to decreased health literacy.To address this concern affecting its patient population, the RCHC implemented a monthly Preventative Health Series (PHS) with the goal of engaging the community in order to improve health literacy. A specific health topic was emphasized each month, such as Diabetes Awareness in November and Mental Health Awareness in December. Infographics providing information about the selected topic were shared throughout the month via social media. Furthermore, during the third week of the month, a doctor or medical student gave an interactive presentation intended to facilitate discussion about the topic among healthcare workers and community members. Due to the coronavirus disease of 2019 (COVID-19) pandemic, these discussions had to be conducted online. However, using an online platform also allowed us to reach a wider audience.